KAJIAN SISTEM PEMANTAUAN PEREDARAN KAYU BUNDAR - Triyono P; Hariyatno D P (Jurnal Penelitian Hasil Hutan, 1996)
The change of assessing  reforestation fund  (DR) and forest product fee (IHH) on logs from official assessment  lo self assessment  by  forest  concession  holder  also changed the  supervision of logs  flow.  The aim of this study  is;  1) lo compare the difference between old system and new system  and   2) lo see  how  the new system  of supervising  as  it operates in the field can be improved.The study  which  was  analysed  using  quantitative  and qualitative approach  showed  that despite of its disadvantage,  self assessment has some advantages with respect 10 flows  of logs because  of simpler  log administrative procedure.   However,  it  decreased  goverment  revenue because  of  illegal  logs and  the delay  in DR payment.   The new system  can  be  refined  by improving  the coordination and communication among  forestry  offices  so the  log flow  can bebetter supervised.Key word :  reforestation fund,  forest product fee, logs flow, official assessment, self assessment.